The Development of Quizziz Assisted Think-Talk-Write Approach Teaching Materials to Improve Students Problem Solving Skills on Social Arithmetic - Bahari, Abdul Ghofur; Setiawan, Wahyu (IKIP Siliwangi, 2024)
The development of this research was driven by the low academic achievement of high school students in the field of social arithmetic. This study aims to develop teaching materials through a test-assisted think-speak-write approach to improve problem-solving skills. The type of research used is development research with the 4D development model (Define, Design, Develop, Dissemination). Research using this model is limited to stage 3 (define, design, develop) due to limited research time. The object of this study was students of class VII at Al-Fatih KBB integrated college with data analysis techniques using descriptive qualitative techniques. Data was collected and then analyzed using Microsoft Excel. Results shows that the feasibility of teaching materials can be seen from the results of the evaluator's assessment, small-scale tests and large-scale tests. At 91% and 95% in the